Inhibition of IL-25/IL-17RA improves immune-related adverse events of checkpoint inhibitors and reveals antitumor activity - Brian S Henick; Xizi Hu; Shoiab M Bukhari; Carly Tymm; Kieran Adam; Shalom Lerrer; Robert J Winchester; Adam Mor (Journal for ImmunoTherapy of Cancer, 2024)
Background Immune checkpoint inhibitors (ICIs) have improved outcomes and extended patient survival in several tumor types. However, ICIs often induce immune-related adverse events (irAEs) that warrant therapy cessation, thereby limiting the overall effectiveness of this class of therapeutic agents. Currently, available therapies used to treat irAEs might also blunt the antitumor activity of the ICI themselves. Therefore, there is an urgent need to identify treatments that have the potential to be administered alongside ICI to optimize their use.Methods Using a translationally relevant murine model of anti-PD-1 and anti-CTLA-4 antibodies-induced irAEs, we compared the safety and efficacy of prednisolone, anti-IL-6, anti-TNFɑ, anti-IL-25 (IL-17E), and anti-IL-17RA (the receptor for IL-25) administration to prevent irAEs and to reduce tumor size.Results While all interventions were adequate to inhibit the onset of irAEs pneumonitis and hepatitis, treatment with anti-IL-25 or anti-IL-17RA antibodies also exerted additional antitumor activity. Mechanistically, IL-25/IL-17RA blockade reduced the number of organ-infiltrating lymphocytes.Conclusion These findings suggest that IL-25/IL-17RA may serve as an additional target when treating ICI-responsive tumors, allowing for better tumor control while suppressing immune-related toxicities.